Analysis of PER, DER, and ROA on the Textile Companies’ Performance Listed on Indonesian Stock Exchange - Susanti, Fathonah Eka; Laras, Titi (KINERJA, 2021)
Securities trading is a way to attract public funds in this case investors to develop an economy where the fund is the capital that the company needs to expand its business. The purpose of this study is to find out how much influence price earning ratio, debt to equity ratio, and return on assets, together and partially significant on the share price of textile industry subsectors for the period 2005-2012. The study used classic assumption tests (normality tests, multicolinete tests, autocorroration tests, heteroskedasity tests), regression tests (F and t tests). The samples used were textile industry subsectors on the Indonesia Stock Exchange from 2005 to 2012. Variables used price earning ratio, debt to equity ratio, and ratio on asset as independent variables and share prices as dependent variables. The results of this study mention that price earning ratio, debt to equity ratio, and return on assets are influential together and partially significant to the share price of textile industry subsectors on the Indonesia Stock Exchange in 2005-2012.Keywords: Price Earning Ratio (PER), Return on Asset (ROA), Debt to Equity Ratio (DER)